Tanzania : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for waiver of Performance Criterion- Staff Report; Staff Statement; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2004)
Tanzania showed commendable growth owing to its macroeconomic stability and structural reforms under the Poverty Reduction and Growth Facility (PRGF) Arrangement. Executive Directors commended these developments, and agreed that debt relief under the enhanced Heavily Indebted Poor Countries Initiative has helped Tanzania to maintain debt sustainability. They stressed the need to accelerate structural reforms, maintain sound fiscal position, debt sustainability, strengthen governance, and improve tax policy. They welcomed the anticorruption strategy; and agreed that Tanzania has successfully completed the first review under the PRGF, and approved waiver.